Feasibility Study of Tank Car Investment for Fuel Distribution at Fuel Terminal in Garut Area - Salvia Fitrianingrum; Kushariyadi Kushariyadi; Muhammad Ayyasi Resionda (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study examines the effectiveness and economic feasibility of purchasing and leasing a fleet of tankers for fuel distribution to gas stations. The fleet used consists of 10 units with various capacities. The results show that the initial investment for purchasing reached Rp19,377,842,022.10, while the rental cost was only Rp17,925,390,000. The annual operating cost for purchasing was recorded at Rp53,193,591,706.93, higher than the rental cost of Rp51,585,649,513.20. Despite the higher operating costs, the annual depreciation for purchasing was recorded at Rp1,695,561,201.60 with a BEP value of Rp150,600,071,968.05. From a financial perspective, the IRR for leasing reached 18%, slightly lower than the purchase which reached 19%. However, the PV value of income from leasing is greater, namely Rp199,184,815,732.30, compared to purchasing which is only Rp199,509,891,668.76. Based on the analysis of the profitability index and the investment payback period, the leasing scheme is proven to be more effective and feasible than purchasing, both in terms of initial costs, operational costs, and long-term profit potential, and is more feasible to implement.